2019
DOI: 10.3390/metabo9030047
|View full text |Cite
|
Sign up to set email alerts
|

Defining Metabolic Rewiring in Lung Squamous Cell Carcinoma

Abstract: Metabolomics based on untargeted flow infusion electrospray ionization high-resolution mass spectrometry (FIE-HRMS) can provide a snap-shot of metabolism in living cells. Lung Squamous Cell Carcinoma (SCC) is one of the predominant subtypes of Non-Small Cell Lung Cancers (NSCLCs), which usually shows a poor prognosis. We analysed lung SCC samples and matched histologically normal lung tissues from eight patients. Metabolites were profiled by FIE-HRMS and assessed using t-test and principal component analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
2
3
0
Order By: Relevance
“…Glycerol is converted to glycerol-3-phosphate and glycerol-3-phosphate is essential for cell proliferation and growth [23]. The increased glycerol-3-phosphate level was reported in the lung SQCC tissue, compared to normal tissue [24]. In our study, increased levels of glycerol-3-phosphate were observed in the lung SQCC lines with highmetastatic potential, compared with those in normal cells.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Glycerol is converted to glycerol-3-phosphate and glycerol-3-phosphate is essential for cell proliferation and growth [23]. The increased glycerol-3-phosphate level was reported in the lung SQCC tissue, compared to normal tissue [24]. In our study, increased levels of glycerol-3-phosphate were observed in the lung SQCC lines with highmetastatic potential, compared with those in normal cells.…”
Section: Discussionsupporting
confidence: 61%
“…Our study revealed that hypoxanthine and inosine concentrations were increased with increasing metastatic potential. In the previous study, higher levels of hypoxanthine and inosine were observed in lung SQCC tissue, compared to normal tissue [24]. Significantly higher levels of adenosine triphosphate (ATP) and adenosine diphosphate (ADP) were suggested as characteristic of lung SQCC tissues versus lung adenocarcinoma and large cell carcinoma [37].…”
Section: Discussionmentioning
confidence: 89%
“…In vivo ndings of the currently presented research include high amplitude choline concentration for metastatic colon adenocarcinoma as well as prominent lactate peak for lung SCC in a patient with widespread distant metastases, who unfortunately expired after 3 months. Tumor marker concentrations have been consistent with tumor histopathology and have been con rmed in other studies (22,(46)(47)(48)(49)(50)(51)(52)(53)(54). Peak appearance was categorized in three different concentrations de ned as 1+, 2 + and 3+, which may help simply de ne the pathological characteristics in future research.…”
Section: Concentration Estimation Of Biomarkerssupporting
confidence: 74%
“…LUSC, which usually has a poor prognosis, is one of the major subtypes of lung cancer, and is difficult to treat as patients tend to be older and have a higher incidence of comorbidities (17,18). The occurrence of lung cancer is an intricate biological process involving multiple steps and factors, and is closely related to changes in genetic information.…”
Section: Discussionmentioning
confidence: 99%